Penanaman Nasionalisme Pelajar Milenial Tanpa Narkoba Melalui Pementasan Monolog - Natal Kristiono; Indri Astuti (Ganaya : Jurnal Ilmu Sosial dan Humaniora, 2019)
Nationalism needs to be planted to the next generation of this milestone of struggle which will then be continued by the next generation. Drug abuse becomes a problem that cannot be overcome. Many cases illustrate the more terrible problem. Many cases illustrate the horrific problems. To solve the problem of drug abuse cannot only be solved by one party. In accordance with the formulation of the problem and the purpose of the study, the focus of the research was the cultivation of millennial nationalism without drugs applied in the Texmaco Pemalang Vocational School which included personal and procedural procedures. Current millennial students with good technological mastery can access information quickly but with negative impacts that also need to be watched out. There have been many patterns of drug abuse prevention. The pattern of drug prevention continues to be developed as a form of our concern in overcoming the threat of this country. Students have the opportunity to explore information, process and convey to others as their role in education